2023
DOI: 10.7150/thno.84059
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioned extracellular vesicles from hypoxic microglia reduce poststroke AQP4 depolarization, disturbed cerebrospinal fluid flow, astrogliosis, and neuroinflammation

Abstract: Background: Stroke stimulates reactive astrogliosis, aquaporin 4 (AQP4) depolarization and neuroinflammation. Preconditioned extracellular vesicles (EVs) from microglia exposed to hypoxia, in turn, reduce poststroke brain injury. Nevertheless, the underlying mechanisms of such effects are elusive, especially with regards to inflammation, AQP4 polarization, and cerebrospinal fluid (CSF) flow. Methods: Primary microglia and astrocytes were exposed to oxygen-glucose deprivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Furthermore, M2 microglia-derived EVs could transfer miR-137 to neurons, and miR-137 could inhibit neuronal apoptosis by targeting Notch 1 [ 133 ]. Another study found that EVs from microglia pre-exposed to OGD could not only inhibit neuroinflammation, AQP4-mediated depolarization, brain edema, and astrogliosis, but also promote CSF flow, cerebral blood circulation, and neurological recovery [ 134 ]. However, the mechanism needs to be further clarified.…”
Section: Role Of Nvu-evs In Ismentioning
confidence: 99%
“…Furthermore, M2 microglia-derived EVs could transfer miR-137 to neurons, and miR-137 could inhibit neuronal apoptosis by targeting Notch 1 [ 133 ]. Another study found that EVs from microglia pre-exposed to OGD could not only inhibit neuroinflammation, AQP4-mediated depolarization, brain edema, and astrogliosis, but also promote CSF flow, cerebral blood circulation, and neurological recovery [ 134 ]. However, the mechanism needs to be further clarified.…”
Section: Role Of Nvu-evs In Ismentioning
confidence: 99%
“…Interestingly, recent evidence from preclinical models of acute ischemic stroke has found that sEVs derived from M2 microglia 20,21 or brain endothelial cells 22 can reduce the damage of the BBB, increasing the expression of CLDN5 in brain tissue. However, there are not information whether circulating or placenta-derived sEVs may regulate brain levels of CLND5, neither regarding its potential implication in the disruption of the BBB observed in PE.…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, ShamsEldeen et al, 19 showed that PE-like syndrome in rats (i.e., generated by oral administration of nitric oxide inhibitor) is associated with reduced brain protein levels of CLDN5 and high-water content of the brain. Interestingly, recent evidence from preclinical models of acute ischemic stroke has found that sEVs derived from M2 microglia 20,21 or brain endothelial cells 22 can reduce the damage of the BBB, increasing the expression of CLDN5 in brain tissue. However, there are not information whether circulating or placenta-derived sEVs may regulate brain levels of CLND5, neither regarding its potential implication in the disruption of the BBB observed in PE.…”
Section: Introductionmentioning
confidence: 99%
“…Upon the occurrence of a stroke, these immune cells are activated in a dynamic process, providing both neurotoxic and neuroprotective effects. Intralesional microglia and newly recruited microglia assume an anti-inflammatory phenotype at the early stages of ischemia but gradually transform into a pro-inflammatory phenotype in lesion-neighboring areas [2]. These different biological properties of microglia exposed to stroke correlate with distinct phenotypes, as suggested by the pro-inflammatory M1 phenotype and the anti-inflammatory M2 phenotype [3].…”
Section: Introductionmentioning
confidence: 99%